LEVERAGE FACTORS IN ENHANCING FOOD COMMODITIES PERFORMANCE - Soetrisno Soetrisno; Joko Soejono; SRDm Rita Hanafie (Socio-Economics/Agribusiness Department, 2016)
The research goals are (1) to analyze potential of rice, corn, and soybean commodity; (2) technology replication of rice, corn, and soybean commodity cultivation; (3) post-harvest implementation system of rice, corn, and soybean commodity cultivation; and (4) leverage factors that stimulate sub-sector for rice, corn, and soybean commodity. The research locations were Sumenep, Sampang, Bojonegoro, Lamongan, Tulungagung, Blitar, Situbondo, and Banyuwangi Regency. Data collection technique in this research used Snowball Sampling method and it was also conducted by soil sampling to know content of soil nutrient for organic C, Nitrogen, Phosphate, and Potassium in each commodity land (rice, corn, and soybean). Data used in this research was primary and secondary data. Data analysis method used are (1) descriptive analysis; (2) LQ; (3) Cobb-Douglas production function; (4) Income analysis; and (5) Contribution analysis. The research results show that (1) rice and corn needs in East Java still in surplus level, however it was deficit for soybean; (2) basis sector could be made as mainstay in order to improve an area’s economic level through economic growth, especially for three food commodities of rice, corn, and soybean. However, soil fertility was decreasing, particularly for organic C (under 2 percent). Besides, agricultural land in many areas are suffered by degradation due to land conversion. The implementation of cultivation and post-harvest technique have been suitable with local wisdom and varied depending on geographic and topographic condition, rainfall pattern, habit, farmer resource quality, information, and agribusiness capital. Leverage factors for soybean that could stimulate the improvement of food commodity production in East Java is land area and fertilizer use variable. Moreover, the variable that affects production decrease is technology application. Leverage factors for rice are variable of land area, organic fertilizer use, inorganic fertilizer use, seeds, workers, and technology. Then, the leverage factor of corn commodity are land area, organic fertilizer use, inorganic fertilizer use, and seeds.